Ultra-thin broadband metamaterial absorber - Liu, Yahong; Gu, Shuai; Luo, Chunrong; Zhao, Xiaopeng (Applied physics. A, Materials science & processing, 2012)
The design, fabrication, and measurements of a broadband metamaterial absorber are reported. The proposed metamaterial absorber consists of circular metallic patches and a metallic ground plane separated by a dielectric layer. Increasing the number of metallic patches can broaden the frequency range when their resonances are closely packed together, thereby resulting in a broadband resonance. Experimental results show that the proposed absorber has high absorptivity, with a full width at half maximum absorption bandwidth of 2.8 GHz and the relative FWHM absorption bandwidth of 25.3 %. In addition, the absorber can operate at a wide range of incident angles under both transverse electric and transverse magnetic polarizations.